TRANSLATING MEDICAL TEXTS FOR LEGAL PURPOSES: A GROWING CHALLENGE FOR COURT TRANSLATORS AND INTERPRETERS - KOŚCIAŁKOWSKA-OKOŃSKA, Ewa (Comparative Legilinguistics, 2012)
Medical translation has been an area of an increased growth in the demand for translation services. It is considered to cover an extensive variety of genres, starting from hospital discharge reports, epicrises, specialist articles in medical journals, patient information leaflets (PILs) or instructions for use (IFU). It also has entered the area of activity of court translators due to e.g. migration or Poland’s membership in the EU and resultant EU-law implementation procedures (i.e., implementation of the Medical Devices Directive 93/42/EEC) and commercialisation of medical devices, thus generating the need to deal with an array of texts from the entire realm of various fields of medicine, and related disciplines (pharmacy, pharmacology, biology, etc.). Court translators are therefore facing difficulties and at the same time challenges, among which most important are the lack of medical knowledge, medical terminology (including acronyms and abbreviations) or medical phraseology in general. This entails the development of a new professional approach towards proceeding with such tasks, and requires constant improvement of skills and knowledge as well as special competencies that might be of help for translators (for this reason the notions of professionalism and translation competence shall be briefly elucidated). The focus of the article is placed on translation of medical texts seen from the point of view of translators and the purpose of translation, and not from the perspective of users, thus the approach is translator-centred.